Glycerol-derived magnetic mesoporous Fe/C composites for Cr(VI) removal, prepared via acid-assisted one-pot pyrolysis. (August 2019) - Cui, Yanbin; Atkinson, John D.
Abstract: Rapid increases in biodiesel use results in a surplus of its production by-product, glycerol, exceeding demand by traditional applications. In this study, Fe/C composites are prepared from glycerol-based precursors that include a dissolved iron salt via one-pot, two-stage pyrolysis. The first heating stage dehydrates, polymerizes, and carbonizes glycerol via acid-assisted pyrolysis while homogeneously dispersing a precipitated iron salt throughout the generated carbon matrix. The second stage develops porosity in the carbon support while reducing impregnated iron nanoparticles. Carbon supports with tailored physiochemical properties are generated by varying the dehydration acid (H2 SO4 or H3 PO4 ). Fe/C samples are predominantly mesoporous, with specific surface areas up to 560 m 2 /g and bulk iron contents up to 8.9 wt%, primarily as partially reduced Fe3 O4 . Cr(VI) removal follows the Freundlich model, reaching 107 mg/g at pH = 5. Mesoporous Fe/C composites are magnetic, allowing collection for reuse. After 4 use/recovery/reuse cycles, performance drops by < 25% when the products are applied in an actual wastewater system. Overall, the magnetic mesoporous Fe/C composite materials are straightforward to produce from waste glycerol and exhibit potential for environmental application in aqueous systems. Highlights: Acid-assisted glycerol carbonization generates carbon with tailored porosity/chemistry. Meso- and macroporosity in Fe/Cs provide space for up to 107 mg/g Cr(VI) removal. Embedded iron NPs are magnetic, facilitating sample recovery for regeneration and reuse. Fe/GP-C has 78% performance recovery after 4 reuse cycles in wastewater.